Empowering Women through Financial Inclusion and Governance: Evidence from 30 Developing Economies - Mahwish, Sadia; Bashir, Furrukh; Abbassi, Faisal Azeem; Khan, Shahbaz Ali (iRASD Journal of Economics, 2024)
Gender equality is rooted in the capacity of individuals to independently make decisions regarding their social, political, and economic well-being. Unfortunately, women encounter diminished opportunities for engagement in these spheres, particularly evident in developing economies. UN-SDGs has placed gender equality as a 5th goal in the framework. This study aims to elucidate pathways for women empowerment by investigating the moderating influence of governance within the realm of financial inclusion. Panel data analysis has been employed for 30 developing economies for the time of 2004 to 2020.Data sources are World Development Indicators (WDI) and the International Country Risk Guide (ICRG). The labor force participation rate (LFPRF) was employed as a proxy for women empowerment and is treated as dependent variable. Governance and Financial Inclusion were examined as independent variables, with domestic credit to the private sector (DC) representing financial inclusion and governance stability (GS) acting as a proxy for governance. Gross capital formation (GCF) and gross domestic product per capita (GDPPC) were included as control variables. Ordinary Least Squares (OLS), FE, and RE regression models were considered appropriate after applying pre diagnostic tests. The study also employed Arellano Bond model for robustness. The Results indicated that 1 % increase in DC increased LFPRF by 1.05%,16%, and 0.16% in OLS, FE, RE respectively. Similarly, 1 % increase in GS increases LFPRF by 2.49% in OLS model and by 0.13% in both FE and RE model. The study also discussed the strategies to promote women empowerment through planned interventions in financial inclusion and governance.